Conditions affecting ergothioneine levels in Mycobacterium smegmatis & the attempted isolation of Î±-N, N, N-Histidine methyltransferase, the first enzyme in ergothioneine biosynthesis - Williams, Monique J (Division of Medical Microbiology, 2015)
Includes bibliographical references (leaves 120-133).